ANALISIS GEOMEKANIKA SATU DIMENSI UNTUK PENENTUAN BATAS MAKSIMUM TEKANAN INJEKSI C02 PADA INTERVAL - Fahri Satrio Utomo, Maulana
Indonesia is committed to reducing carbon emissions and has previously announced its commitment to achieve net zero emissions by 2060 or earlier. Carbon capture, utilisation and storage (CCUS) is one of the most promising emission reduction technologies today. The main objective of CCUS activities is to ensure that CO2 remains in the subsurface for an indefinite period of time as its leakage can result in various environmental, health, safety, economic and socio-political risks. Injection of CO2 into the subsurface in large quantities can be associated with a number of geomechanical risks. One-dimensional geomechanical model analysis includes vertical stress, pore pressure, rock elastic property, rock strength, horizontal stress, and stress orientation using core rock data and talikawat logs. The determination of the maximum limit of CO2 injection in the reservoir depends on the insitu pressure conditions that drive fault reactivation. Fault reactivation can be quantified using 3D mohr circles and failure envelopes. The modelling results show that the tectonic regime in the study area is a strike-slip regime with a maximum horizontal stress direction (SHmax) of north-south as seen from the appearance of induced tensail in the image log data. Fault reactivation analysis was conducted using friction coefficients of 0.6 and 0.89. The fault in the study area has a relatively high risk of reactivation requiring an increase in average pore pressure of about ~507 psi using a friction coefficient of 0.6. While using a friction coefficient of 0.89 has a relatively low risk of reactivation requiring an increase in average pore pressure of about ~1197 psi.